Metaphoric semiosis: a Peircean perspective / Semiose metafórica: uma perspectiva peirceana (Revista de Estudos da Linguagem, 2020)
Abstract: This article presents how metaphoric semiosis develops from the perspective of Peircean semiotics. The study takes as theoretical framework the general foundations of metaphor as described by classical theories, its recognized cognitive nature and the theory of signs developed by Charles S. Peirce (1839-1914) based on his three phenomenological categories. This is on the assumption that the application of Peirce’s broad conceptual tools – philosophical and semiotic – to his concept of metaphor as a hypoicon and its subdivisions constitutes an original and dynamic theory of metaphor, capable of operationalizing integrated analyzes of multimodal aspects of metaphor. In conclusion, considerations are made about the truth value of a good metaphor according to Peircean theoretical framework.Keywords: metaphor; semiotics; meaning; cognition; iconicity; multimodality. Resumo: Este artigo apresenta a forma como se desenvolve a semiose metafórica sob a perspectiva da semiótica peirceana. O estudo toma como quadro teórico os fundamentos gerais da metáfora descritos pelas teóricas clássicas, sua reconhecida natureza cognitiva e a teoria dos signos desenvolvida por Charles S. Peirce com base em suas três categorias fenomenológicas. Parte-se do pressuposto de que a aplicação do amplo instrumental conceitual de Peirce, tanto filosófico como semiótico, a seu conceito de metáfora como hipoícone e suas subdivisões constitui uma teoria original e dinâmica da metáfora, capaz de operacionalizar análises integradas de aspectos multimodais da metáfora. À guisa de conclusão, são tecidas considerações sobre o valor de verdade de uma boa metáfora de acordo com o quadro teórico peirceano.Palavras-chave: metáfora; semiótica; significação; cognição; iconicidade; multimodalidade.